Hemodynamics of 17-mm vs. 19-mm St. Jude Medical Regent and annulus enlargement. (July 2015) - Prifti, Edvin; Bonacchi, Massimo; Baboci, Arben; Giunti, Gabriele; Esposito, Giampiero; Krakulli, Klodian; Ademaj, Fadil; Kajo, Efrosina; Vanini, Vitttorio
Objective: We aimed to compare early and midterm clinical and hemodynamic outcomes of 17-mm vs. 19-mm St. Jude Medical Regent valves with concomitant aortic annulus enlargement. Methods: Between 1999 and 2012, 20 patients (group 1) underwent first-time aortic valve replacement with a 17-mm St. Jude Medical Regent valve, and 35 patients (group 2) had a 19-mm valve and concomitant aortic annulus enlargement. The mean follow-up was 81 ± 37 months (range 20–110 months). Results: There was one death in group 1 vs. 4 in group 2 ( p  > 0.05). The mean postoperative transprosthetic gradient was 17.5 ± 4.5 in group 1 and 17 ± 6.4 mm Hg in group 2 ( p  = 0.83), and 37 ± 10.7 and 32 ± 13 mm Hg, respectively, under stress ( p  = 0.17). Left ventricular mass and left ventricular mass index were reduced and similar in both groups. Postoperative effective orifice area index was higher in group 2 (0.85 ± 0.17 cm 2  m −2 ) than group 1 (0.76 ± 0.2 cm 2  m −2 ; p  > 0.05). A multivariate Cox model identified a 19-mm valve with aortic annulus enlargement ( p  = 0.032), functional class ( p  = 0.025), reoperation ( p  = 0.04), ejection fraction < 35% ( p  = 0.042), and combined surgery ( p  = 0.04) as strong predictors of poorer overall event-free survival. Conclusions: The 17-mm St. Jude Medical Regent valve may be employed with satisfactory postoperative clinical and hemodynamic outcomes in patients with a small aortic annulus, as an alternative to a larger prothesis with aortic annulus enlargement.